Carbamazepine-induced DRESS syndrome - Díaz-Romero, Hermilio (2019)
Drug reaction with eosinophilia and systemic symptoms (DRESS) is a rare clinical condition. It is presented a case of carbamazepine-induced DRESS syndrome in an alcoholic patient who presented with skin rash and lab tests compatible with hepatitis that improved with steroids and carbamazepine withdrawal.